Knowledge, attitude, and practice toward AI use among health profession students in a Malaysian public university - Faisal, Anis Faeza; Ahmad Mizher, Hussam Abdeljabar; Zaini, Syahrir; Abdallah, Qasem M.; Abdallah, Mohammad (IEEE, 2025)
Abstract— Introduction: Artificial intelligence (AI) has evolved rapidly into an effective tool in educational and healthcare settings. The purpose of this research is to assess the knowledge, awareness, and attitudes of healthcare students regarding AI and its use in medical education. Methods: A webbased survey was distributed through email and WhatsApp to 247 health students at the International Islamic University Malaysia (IIUM). Demographics, Knowledge, Attitude, and Practice (KAP) questionnaire answers, and perceived healthcare education barriers for AI adoption were collected. Associations between variables were analyzed. Results: Of the respondents, 66 (26.7%) were male, and 181 (73.3%) were female. The majority demonstrated a high level of knowledge (72.5%), a strong positive attitude (96.8%), and frequent AIrelated practices (80.6%). Most students recognized that AI requires extensive labeled data for learning, and over half emphasized the importance of understanding AI's ethical implications. The most common AI-related activity was exam preparation. Despite their overall positive attitude, many students do not actively engage with AI tools, indicating potential barriers such as limited access or training. Conclusion: This study highlights a generally positive perception of AI among healthcare students at IIUM Kuantan Campus. However, the gap between positive attitudes and practical engagement suggests a need for improved AI training and accessibility in medical education.